Whither the Black Worker? By Bill Fletcher Jr. (December 2022) - Fletcher, Bill
The Black worker is an accumulation of years of struggle against white supremacy and economic injustice. The fight of the Black worker is not only a fight against racism, but is a fight to transform the agenda of the workers' movement.